Keberlanjutan Pengelolaan Sampah Domestik di Kampung Menoreh, Kelurahan Sampangan, Semarang - Abadi, Ronny Setiawan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Limited capacity of Semarang City’s final disposal site and problems in it’s waste management has motivated the community in Menoreh Neighborhood of Sampangan Sub-district, Semarang Cty to independently manage their domestic waste. This study examines the sustainability of the aforementioned initiative which has stopped for 3 years and has returned operational in 2008. Examinations were completed on the 7 aspects of its sustainability, namely the environmental condition, community’s social-cultural, economic, policy support, technical implementation, institutional, and the reduction of waste. Analysis showed the realization of sustainability in the terms of environmental, economic, policy support, and technical implementation aspects; however the contrary was true in terms of social-cultural, institutional, and the reduction of waste. In general, the aforementioned initiative has failed to fully realize criterion of sustainability. The study recommends refurbishment and improvement of the current waste management facility, socialization and provision of the community waste management appliances, along with proper division of task for waste management.